The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1177/0145561319834862
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Labyrinthine Hemorrhage in Patients With Sudden Sensorineural Hearing Loss

Abstract: To investigate the application of inner ear 3-dimensional fluid-attenuated inversion recovery (3D-FLAIR) magnetic resonance imaging (MRI) in patients with sudden sensorineural hearing loss (SSNHL) accompanied by inner ear hemorrhage. A total of 1252 SSNHL patients who were admitted from January 2010 to April 2018 were included in the study. The patients' clinical features, complete blood counts, coagulation profiles, audiometry data, and MRI scans were retrospectively reviewed. Twenty-four patients had high la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 21 publications
(37 reference statements)
0
20
0
Order By: Relevance
“…Inner ear MRI abnormalities include inner ear haemorrhage, protein deposition and BLB‐B. This is usually due to haemorrhage or inflammation 22,23 . This study found no correlation between TEG and inner ear MRI.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Inner ear MRI abnormalities include inner ear haemorrhage, protein deposition and BLB‐B. This is usually due to haemorrhage or inflammation 22,23 . This study found no correlation between TEG and inner ear MRI.…”
Section: Discussionmentioning
confidence: 62%
“…This is usually due to haemorrhage or inflammation. 22,23 This study found no correlation between TEG and inner ear MRI. In patients with normal MRI, TEG hypercoagulation and hypocoagulation were found in 32% and 8% of patients, respectively, and in patients with abnormal MRI results, TEG hypercoagulation and hypocoagulation were found in 44.2% and 7.7% of patients, respectively.…”
Section: Comparisons To Other Studiesmentioning
confidence: 58%
“…This theory explains why full IAC involvement of tumor is a risk factor of cochlear obliteration. Labyrinthine hemorrhage is another possible cause of cochlear obliteration and can be detected by abnormal hyperintense signal in pre-contrast T1W or FLAIR MRI [Vakkalanka et al, 2000;Chen et al, 2019]. High signal intensity on T1W image is probably caused by intracellular methemoglobin or protein macromolecule deposition following erythrocyte destruction.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the widespread use of Magnetic Resonance Imaging (MRI) acute sensorineural hearing loss (SNHL) due to hemorrhage in inner ear has been reported in the literature [16]. Also, especially in patients with underlying coagulation disorders, cases of SNHL as a result of ILH have been reported [17,18].…”
Section: Discussionmentioning
confidence: 99%